The Influences of Investment Towards Regional Gross Domestic Product (RGDP) in Lampung Province - Habiburrahman HABIBURRAHMAN (Bandar Lampung University, 2015)
This study examines the effect of investment to RGDP. Problems in Lampung province is RGDP growth and investment that fluctuates. It has not been known yet how the contribution of investment to RGDP. By knowing the contribution of these factors, policies can be formulatedto attract investors to invest in Lampung Province. This research used explanatory method that aims to explain the causal relationship between variables and test the hypotheses. This research used secondary data in the form of time-series data for 33 years using simple linear regression analysis with the technique of Ordinary Least Square (OLS) by using the Eviews program version 7.0. The research findings showed that the increase in RGDP relies on investment. Furthermore, this study also found out that increasing the investment is a strategy to increase the RGDP in Lampung Province.